2019
DOI: 10.1016/j.synbio.2019.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic and transcriptional changes in response to pinene tolerance and overproduction in evolved Escherichia coli

Abstract: α-Pinene is an important monoterpene, which is widely used as a flavoring agent and in fragrances, pharmaceuticals and biofuels. Although an evolved strain Escherichia coli YZFP, which had higher tolerance to pinene and titer, has been successfully used to produce high levels of pinene, the pinene titer is much lower than that of hemiterpene (isoprene) and sesquiterpenes (farnesene) to date. Moreover, the overall cellular physiological and metabolic changes caused by higher tolerance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Mostly, CRISPRi applications have been described for the model organism E. coli , for example, to produce various products, such as terpenes [93–96], polyhydroxybutyrate (PHB) [97–101], or alcohols such as n ‐butanol [102] or 1,4 butandiol [103].…”
Section: Metabolic Engineering Applications Of Crisprimentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, CRISPRi applications have been described for the model organism E. coli , for example, to produce various products, such as terpenes [93–96], polyhydroxybutyrate (PHB) [97–101], or alcohols such as n ‐butanol [102] or 1,4 butandiol [103].…”
Section: Metabolic Engineering Applications Of Crisprimentioning
confidence: 99%
“…Furthermore, a different terpene, α‐pinene, which is widely used as a flavoring agent as well as in fragrances, pharmaceuticals, and biofuels, has been produced by a combinatorial approach of CRISPRa and CRISPRi. Thereby, a higher tolerance and titer of α‐pinene was revealed [96].…”
Section: Metabolic Engineering Applications Of Crisprimentioning
confidence: 99%
“…Several studies have demonstrated that E. coli can cope with pinene-induced stress using endogenous genes (37)(38)(39).…”
Section: Improved Pinene Tolerance Using a Multiplexed Sponge Librarymentioning
confidence: 99%
“…UlaR is a regulator of the ula operon that is responsible for L-ascorbate metabolism. UlaE has been reported to significantly enhance pinene tolerance (39), however, the specific mechanism by which this operon increases tolerance is not well understood. AcrR regulates expression of the multidrug efflux pump AcrAB-TolC, which is also known to increase pinene tolerance (37).…”
Section: Improved Pinene Tolerance Using a Multiplexed Sponge Librarymentioning
confidence: 99%
“…The catalytic process of mevalonic kinase and mevalonate diphosphate decarboxylase were identified as the bottlenecks of the MVA pathway in recombinant E. coli [36]. A strain of laboratory involved pinene-producing E. coli strain was whole genome sequenced, then aligned with the E. coli reference strain MG1655 genome sequence, then non-synonymous mutant genes were up and downregulated [37]. Using comparative genomics and transcriptional level analysis, it was shown that mutations and up-regulation of transcription levels of the MEP pathway genes (dxr, dxs, ispH, and ispU) and some protein membrane genes (gsiA, nlpA, sufBCDS, opgB, setC, oppF, ypjK, btuB, pitA and cusA) are related to increased pinene tolerance and production in E. coli [37].…”
Section: E Colimentioning
confidence: 99%